Social Conformity in Immersive Virtual Environments: The Impact of Agents’ Gaze Behavior - Kyrlitsias, Christos; Michael-Grigoriou, Despina; Banakou, Domna; Christofi, Maria Dolores (My University, 2020)
Immersive virtual reality (IVR) can induce an experience of “social presence” which can, in turn, increase social influence. Non-verbal behavior such as eye contact is an important component of human communication and, therefore, an important factor in creating social presence. This paper presents an experimental study that elaborates social influence through conformity with a group of virtual agents within an immersive virtual environment (IVE). Specifically, it investigates the impact of the agents’ gaze behavior on social presence and influence. An experiment based on the Asch (1951) paradigm using two levels of agents’ gaze behavior (Eye Contact condition vs. No-Eye Contact condition) was conducted. The results showed that participants conformed with the agents as they gave significantly more incorrect responses to the trials that the agents also gave an incorrect response, compared to those trials that the agents gave correct answers. However, no impact of the agents’ gaze behavior on conformity was observed, even if the participants in the Eye Contact condition reported a higher sense of social presence. In addition, self-reported measures showed a number of social effects that occurred only in the eye contact condition, indicating that the agents’ gaze behavior has an impact on participants’ experience.
Keywords: Agents; Behavioral realism; Conformity; Eye contact; Social influence; Social presence; Virtual reality